2023
DOI: 10.1101/2023.03.06.531220
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Generation of Schwann cell derived melanocytes from hPSCs identifies pro-metastatic factors in melanoma

Abstract: The neural crest (NC) is highly multipotent and generates diverse lineages in the developing embryo. However, spatiotemporally distinct NC populations display differences in fate potential, such as increased gliogenic and parasympathetic potential from later migrating, nerve-associated Schwann cell precursors (SCPs). Interestingly, while melanogenic potential is shared by both early migrating NC and SCPs, differences in melanocyte identity resulting from differentiation through these temporally distinct progen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 61 publications
0
1
0
Order By: Relevance
“…Currently, melanocytes can be derived from induced pluripotent stem cells (iPSC) using multiple methods 32,33 . A recent study showed that the melanocytes derived from temporally distinct iPSC-derived progenitors differ in their pigmentation, migration and proliferation potential 34 . Another study identified a stem cell population in the interfollicular epidermis, which can give rise to pigmented melanocytes 35 .…”
Section: Introductionmentioning
confidence: 99%
“…Currently, melanocytes can be derived from induced pluripotent stem cells (iPSC) using multiple methods 32,33 . A recent study showed that the melanocytes derived from temporally distinct iPSC-derived progenitors differ in their pigmentation, migration and proliferation potential 34 . Another study identified a stem cell population in the interfollicular epidermis, which can give rise to pigmented melanocytes 35 .…”
Section: Introductionmentioning
confidence: 99%